PENGARUH OBAT KUMUR HERBAL DENGAN KANDUNGAN ZAT AKTIF FLAVONOID, SAPONIN, DAN TANIN TERHADAP HALITOSIS (STUDI LITERATUR) - Eddea Marselyna A.D.; Riani Setiadhi; Vinna Kurniawati Sugiaman (Universitas Hang Tuah, 2022)
Introduction: Herbal mouthwash has been developed for its antibacterial properties. Halitosis is bad breath that comes from the mouth. Volatile sulfur compounds (VSCs) are the result of oral bacterial activity production, by Porphyromonas gingivalis which is an gram-negative anaerobic bacteria causing halitosis. Flavonoids have the potential to be an antioxidant and have antibacterial, anti-inflammatory, anti-allergic and anti-thrombotic activities, while saponins and tannins are a group of active plant compounds that are phenolic, have a septic taste and antibacterial activity. The aim of this literature study was to improve knowledge about the effect of herbal mouthwashes with active substances of flavonoids, saponins and tannins on halitosis. Methods: Literature review using research results, articles and other literatures related to herbal mouthwash and medicinal plant content against halitosis. Results: Some researchers had shown that herbal mouthwashes with antibacterial content in the form of flavonoids, saponins and tannins could inhibit the growth of oral bacteria such as Streptococcus mutans, Porphyromonas gingivalis and Streptococcus sanguinis, which would inhibit plaque formation, reducing halitosis, overcoming gingivitis, increasing salivary pH and reducing salivary viscosity. Conclusion: Based on the search results of the search, it can be concluded that herbal mouthwash containing active substances of flavonoids, saponins and tannins has an effect in overcoming halitosis.